Dermal Absorption Of Bisphenol A Through Thermal Paper Receipts: An Alarming And Overlooked Occupational Hazard - Usman Ayaz Khan; Reda Ayaz; Fozan Fahad Memon (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Bisphenol A (BPA) (C15H16O2; 2,2-bis(4-hydroxyphenyl) propane) is a synthetic xenoestrogen produced in large quantities to synthesize polycarbonate plastics. Unconjugated BPA is found in thermal paper receipts where it is present as a colour-developing additive. This unconjugated form found in thermal paper receipts can enter the body through inhalation or dermal contact and is a serious hazard for occupational groups since it can cause endocrine disruption. Furthermore, BPA is associated with cardiovascular and reproductive diseases and insulin resistance.1 The presence of BPA in thermal receipts has detrimental effects, especially on occupational groups, but has received little public scrutiny. Distinct molecular pathways have been identified by studies on BPA exposure. BPA mimics estrogen, causing endocrine disruption; its (BPA) estrogenic potency for non-nuclear estrogen receptors (ER) is similar to estradiol, causing cell function changes at concentrations of 1 picomolar (PM). Estrogen-related receptor Gamma (ERR Gamma) has also been shown to be stimulated by BPA.2,3 Studies show implicated in BPA-induced breast cancer through ERR Gamma-dependent signalling pathway.3 Furthermore, BPA can also damage DNA, causing carcinogenesis and teratogenesis.2 According to studies, the BPA intake of occupational workers through thermal paper receipts was 0.95 Mug/kg bw/day, which was considerably larger than the BPA exposure of the college-age population at 0.05 Mug/kg bw/day.3 This dermal transfer is ten times higher if the skin is humid or greasy.4 Moreover, BPA concentration in urine samples of six recruited volunteers simulating cashiers was found to be three times higher after they had handled thermal papers.3 In women, BPA has been shown to cause polycystic ovarian syndrome and adverse pregnancy outcomes. Male workers exposed to BPA exhibited lower sex drive, increased problems with erections and ejaculation, and diminished sexual satisfaction.3 A strong correlation was demonstrated between urinary BPA levels and the risk of diabetes in numerous studies. High urinary and serum BPA concentrations were also tied to cardiovascular diseases.5 It is long overdue for the world to recognize the hazardous effects of BPA through dermal absorption, especially among the occupational groups. Workers should be educated regarding the adverse effects of BPA and should be advised to handle thermal paper receipts with proper precautions. workers should be educated to wear gloves and wash their hands thoroughly after handling receipts. In addition, less harmful alternatives to BPA should be used and a gradual shift towards electronic receipts.